2022
DOI: 10.1007/s40123-022-00620-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Literature Review, Social Media Listening, and Qualitative Interview Research Methods in Generating Patient-Reported Symptom and Functional Impact Concepts of Presbyopia

Abstract: Introduction To compare the insights obtained about the experience of individuals with presbyopia (age-related impaired near vision) across three different sources of qualitative data: a structured targeted literature review, a social media listening (SML) review, and qualitative concept elicitation (CE) interviews with individuals with presbyopia and healthcare professionals (HCPs). The number of concepts identified, depth of data, cost and time implications, and value of the patient insights gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…This study also highlights that social media posts from patients and caregivers may provide real-world insights into treatment perceptions and quality of life, as previously shown in other studies [ 34 ]. It would also be interesting to cross-reference this or a future study applying our methodology with other qualitative studies on patients with advanced BC to compare the different signals and analyze their potential complementarity [ 16 ]. The extension of our research method to other countries or regions may be also valuable to identify initiatives that could improve treatment perceptions, quality of care, and quality of life for patients with BC and their caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also highlights that social media posts from patients and caregivers may provide real-world insights into treatment perceptions and quality of life, as previously shown in other studies [ 34 ]. It would also be interesting to cross-reference this or a future study applying our methodology with other qualitative studies on patients with advanced BC to compare the different signals and analyze their potential complementarity [ 16 ]. The extension of our research method to other countries or regions may be also valuable to identify initiatives that could improve treatment perceptions, quality of care, and quality of life for patients with BC and their caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to exploring patients’ and caregivers’ perspectives on cancer is to use social media. Social media offer unprompted discussions between patients and caregivers, which may capture more genuine perspectives than traditional surveys, questionnaires, or interviews [ 14 - 16 ]. Social media also allow the collection of data from a much broader, geographically dispersed sample (ie, from a wide range of countries or locations), which may mitigate issues with sample size when examining very specific, nuanced patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…We have been involved in developing quality-of-life questionnaires for macular degeneration, 83,84 visual impairment, [85][86][87][88][89][90] and presbyopia. [91][92][93] With time, we have had to develop some further to remain relevant to changing lifestyles and impact of social media, 94,95 especially the ubiquitous digital environment. 96,97 We have demonstrated that they are influenced by whether they are self-completed or the questions are posed to patients, so this needs to remain the same if scores are to be compared over time or across patients/treatments.…”
Section: Assessment Of Functional Vision Eye Focus/ Accommodationmentioning
confidence: 99%
“…Given the dramatic growth in social media use, social media listening (SML) is increasingly being used to gather insights and information on patient experience across a variety of diseases and treatments [ 21 23 ]. Over the last few years, different SML studies have been published investigating the patient experience also in ophthalmologic conditions such as dry eye disease, presbyopia, retinal detachment, or amblyopia [ 24 28 ], as well as describing ophthalmology information available on social media platforms like Reddit, Instagram, Facebook, Twitter, or LinkedIn [ 29 32 ]. Data from SML exploring patient experience with presbyopia is limited to two publications which evaluated data acquired up to August 2017 [ 25 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, different SML studies have been published investigating the patient experience also in ophthalmologic conditions such as dry eye disease, presbyopia, retinal detachment, or amblyopia [ 24 28 ], as well as describing ophthalmology information available on social media platforms like Reddit, Instagram, Facebook, Twitter, or LinkedIn [ 29 32 ]. Data from SML exploring patient experience with presbyopia is limited to two publications which evaluated data acquired up to August 2017 [ 25 , 28 ]. These studies explored how individuals with presbyopia used social media to describe their experiences and confirmed presbyopia has a substantial impact on an individual’s daily life; however, these studies did not report on specific patients’ perceptions or outcomes by type of PCIOL [ 25 , 28 ].…”
Section: Introductionmentioning
confidence: 99%